Увлекательные путешествия в Древний Египет - Кошечкина В. Г. (Увлекательные путешествия, 2000)
Экземпляры: (20170222) / Инвентарный номер: 36556 / Цена: 32.00 / Сис.шифр: 63.3 / Авт.знак: У 19 / ББК: 63.3(0)31